Dynamic of Nutrients in a Recirculating Aquaponic System Using Red Tilapia (Oreochromis Sp.) and Lettuce (Lactuca Sativa Varlongifolia) - Rafiee, Gholamreza (2003)
A series of experiments were conducted to evaluate the fish and vegetable production in a recirculating aquaponic system In the first experiment, the efficiency of three recirculating aquaculture systems (plant as a biofilter, a simple handmade- biofilter and combination of both plant and biofilter) in the production of fish and removal of N-compounds were evaluated. It was concluded that all the systems were efficient both in the removal of N-compounds as well as giving high red tilapia (Oreochromis sp.) and lettuce (lactuca sativa var longifolia) production. Within a period of fish culture (15 weeks), and a period of lettuce culture (5 weeks), the yield of red tilapia and lettuce ranged from 13.61 to 19.41 kg/m3 and from 0.851 to 2.87 kg/m2 in the hydroponic area, respectively. Based on the results of the first experiment, the system with the use of plant as a biofilter was selected as a model for investigation of the nutrient removal and reabsorption in an aquaponic system The main parts of the system consisted of a black fiberglass tank (110L x 84 W x 100 H cm) equipped with three hydroponics troughs (110L x 30 W x 5 cm Depth), and a submersible pump (Model Aqua, 1500) for recirculating the water through the culture system In the second, third and fourth experiments, the total ammonia excretion by red tilapia (the endogenous ammonia excretion related to catabolism of body protein and exogenous ammonia excretion related to metabolism of feed protein), as well as gaseous ammonia escape rate during different stages of its growth from the culture system were evaluated. It was found that the weight of fish significantly affected ammonia excretion. The rate of total N content of feed excreted by red tilapia ranged from 31.10 to 54.20% for 20-200g red tilapia On average, 39.54% of the nitrogen content of fish feed was excreted as ammonia-N by red tilapia. Water recycling influenced the escape of ammonia due to ventilation an in the culture system. However, the rate of ammonia escaping from the system, decreased inversely with an increase in the fish weight. The percentage of escaped ammonia ranged from 7-72% of total ammonia excreted by fed fish.